Differential protein expression identified by digital spatial profiling (DSP) in the hippocampi of resilient individuals: Human neuropathology: AD neuropathology. (7th December 2020) - Walker, Jamie M.; Dehkordi, Shiva Kazempour; Richardson, Timothy; Zare, Habil; Orr, Miranda E.
Abstract: Background: An intriguing group of individuals, termed "resilient", demonstrate neuropathologic changes consistent with Alzheimer disease (AD), yet display no cognitive impairment. Studies have reported less neuronal loss overall, less gliosis, and fewer comorbidities (such as cerebrovascular disease) in these individuals. We sought to analyze protein expression in and around normal and neurofibrillary tangle (NFT)‐bearing neurons in these individuals as compared to those with cognitive decline. Method: Utilizing Nanostring's GeoMx™ Digital Spatial Profiling (DSP) technology, we compared individuals with AD neuropathologic change and dementia (n = 6) to individuals with AD neuropathologic change and no dementia (n = 8). The DSP panel allowed for spatial analysis of the level of expression of 89 different proteins in multiple regions of interest on formalin‐fixed paraffin embedded sections. We analyzed hippocampal sections, with our regions of interest (ROIs) being NFT‐bearing neurons, non‐NFT‐bearing neurons, and their immediate neuronal microenvironments (50 μm diameter surrounding the neuronal cell body) (Figure 1). Result: Analyses identified 11 proteins having differential expression in tangle‐bearing neurons when comparing resilient to demented individuals. These included IDH1, GFAP, CD68, IDE, SYP and Histone H3. In addition, IDH1, CD68 and SYP were differentially expressed in the environment of normal and tangle‐bearing neurons when comparing resilient to demented individuals. IDH1 displayed significantly lower expression in the resilient individuals. It is thought that IDH1 is upregulated under energetic and oxidative stress. Similarly, PINK1 (which is upregulated in response to mitochondrial dysfunction and oxidative stress) displayed lower expression in the environment of normal and tangle‐bearing neurons in the resilient. Therefore, we hypothesize that there is less energetic and oxidative stress in the resilient individuals. Synaptophysin (SYP) is increased in the resilient, which likely indicates better maintenance of neuronal synapses and synaptic connections. Furthermore, neurofilament light chain (NEFL) and ubiquitin c‐terminal hydrolase (Park5) expression were higher in the resilient compared to the demented in the environment of NFTs. These differences all suggest healthier intact axons, dendrites and synapses in the resilient. Conclusion: In conclusion, resilient individuals display protein expression patterns suggestive of an environment containing less energetic and oxidative stress, which in turn results in maintenance of neurons and their synaptic connections.